Harmonics Analysis and Design of Passive Filter For Low Voltage Distribution System - Chan, Chee Meng (2000)
Power quality is an important and growing concern for utility and facility engineers. The power problems are further aggravated with the rapid increase in the utilisation of non-linear devices. Non-linear devices like computer, uninterruptable power supply, electronic lighting ballast, and motor controller generate harmonics which can put thermal stress on cables and electrical equipment. In addition, telecommunication systems may experience electromagnetic interference from the harmonic noise on the power line. This report presents the harmonic distortion signatures and characteristics of low voltage single-phase and three-phase non-linear loads and suggest the parallel-tuned passive filter as a means to mitigate the harmonics. The recognition of the harmonic signatures, characteristics, symptoms, and an appropriate duration of power quality monitoring will enable the maintenance personnel a quicker and more effective diagnosis to a harmonic-related power quality problem. Most domestic electrical appliances have a switched-mode power supply. The SMPS generates predominant 3rd, 5th, 7th, and 9th harmonic components with the 5th harmonic as the most significant harmonic voltage component and the 3rd harmonic as the most significant harmonic current component. The connection of different types of single-phase non-linear loads to the same power line generates a resultant harmonic profile, which may differ from the individual harmonic profile. Three-phase non-linear loads like the AC-AC and AC-DC drive machines have their own harmonic profile. For the same type of variable speed drive, a six-pulse and a twelve-pulse converter drive, the harmonic profiles are also different. A six-pulse converter drive draws a series of odd harmonic currents, with the 5th, 7th, 11th, and 17th harmonics as the most significant harmonic components. The most significant harmonic components of a twelve-pulse converter drive are the same but of lower magnitude. Normally, the drives are connected to a three-phase three-wire power system therefore the triplen harmonic currents will not flow out of the system. The single-phase filter unit design consists of a two-stage filtering circuit. Each stage is a parallel-tuned passive filter tuned to the 3rd and 5th harmonic frequencies. Simulation results indicate the effectiveness of the filter unit to trap the 3rd and 5th harmonic currents. Hence, the 3rd and 5th harmonic currents from single-phase loads will be prevented from flowing back into the power system, resulting in an overall reduction of the 3rd and 5th harmonics in the neutral conductor.